EGG STOCKING OF Euschistus heros (FABRICIUS) (HEMIPTERA: PENTATOMIDAE) TO MAXIMIZE PRODUCTION OF THE EGG PARASITOID Telenomus podisi ASHMEAD (HYMENOPTERA: SCELIONAE) - de Macedo Almeida, Wellington Souza [UNESP] (2023)
Among the phytophagous insects that attack the soybean crop, the brown bug, Euschistus heros (Fabricius, 1794) (Hemiptera: Pentatomidae) stands out because of its competitive ability in relation to other pentatomids and because it is the most abundant species in the Neotropics, including Brazil. However, the use of Telenomus podisi Ashmead (Hymenoptera: Scelionae) as biological control tool have been studied. This work aimed to study how 3 different materials and 6 storage periods, at 4 temperatures of parasitized and non-parasitized eggs of E. heros could interfere with the biological characteristics of T. podisi. The best biological parameters were observed when the eggs were stored in nitrogen tank in aluminum at 60 days (0.90 ± 0.02 and 0.98 ± 0.02), while the lowest were observed at 60 days when stored in tubes in biochemical oxygen demand (BOD) (0.00 and 0.00). The highest values of egg-adult period are observed when eggs were stored in tubes for 30 days in freezer (16.86 ± 0.37) and BOD (16.90 ± 0.15). When the pupae of the parasitoid were stored in aluminum tubes at the same temperatures mentioned above for 1, 2, 3, 4 and 5 days, only adults emerged when stored in refrigerator and BOD, presenting highest levels of emergence and sex ratio in BOD. These experiments may contribute to an increased production and the availability of the biological agent throughout the year, regardless of climatic conditions.